ITS Academy: una scommessa vincente? L'istruzione terziaria professionalizzante in Italia e in Europa - Turri, Matteo (Milano University Press, 2023)
Higher technical institutes - known in Italy as ITSs (Istituti tecnici superiori) initially, and ITS Academies since 2022 - were ideated 15 years ago to give technical and vocational school graduates more qualified education and work perspectives, with a view to help the Italian economy grow in terms of innovation. ITSs reflect a commitment to make up for the country's lack of tertiary professional education, which is a major factor in Italy's ranking among the countries with the lowest ratio of tertiary graduates in Europe. The National Recovery and Resilience Plan itself has allocated remarkable resources to strengthen these institutes. This Report traces the difficult evolution of ITSs from 2007 to the present, investigates what their future developments may be, and sheds a light on their limits - in terms of size, diffusion and ability to attract students - by comparing them with tertiary professional education models currently in place in France, Germany, Spain and Switzerland